AVAILABILITY OF GREEN OPEN SPACE IN MEDAN CITY - Tambunan, Ayu Anggraini; Soni, Aprianto (Jurnal Ilmiah Global Education, 2023)
Urban development often prioritizes the economic sector over green open spaces (RTH), which significantly impacts environmental sustainability. Medan City faces challenges in meeting RTH targets, particularly in the context of rapid population growth and limited urban land. This research explores the availability and policies of RTH in Medan City and identifies factors influencing the lack of RTH. The research findings indicate that the implementation of RTH policies in Medan City is still far from the set targets. Despite efforts such as land acquisition and the addition of RTH, deficiencies persist, mainly concerning the community's understanding of the importance of RTH. Therefore, this study recommends an approach of intensification and extensification in RTH development, involving community participation, integrated planning, and the application of Green City concepts to achieve environmental sustainability and community well-being in Medan City.